1998
DOI: 10.1038/eye.1998.48
|View full text |Cite
|
Sign up to set email alerts
|

Clinical applications of chromosome analysis, from fine needle aspiration biopsies, of posterior uveal melanomas

Abstract: Cytogenetic analysis was performed following standard protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…These authors concluded that FNAB of uveal melanoma provided sufficient samples and was reliable for FISH analysis for chromosome 3 or 8 abnormalities. Sisley et al 17 found similar accurate correlation of cytogenetic analysis in FNAB compared with solid tumor samples after enucleation in 10 cases.…”
Section: Commentsupporting
confidence: 51%
“…These authors concluded that FNAB of uveal melanoma provided sufficient samples and was reliable for FISH analysis for chromosome 3 or 8 abnormalities. Sisley et al 17 found similar accurate correlation of cytogenetic analysis in FNAB compared with solid tumor samples after enucleation in 10 cases.…”
Section: Commentsupporting
confidence: 51%
“…Therefore, the application of FISH to FNAB is considered a reliable method for detecting genetic prognostic parameters, and cytologic material obtained using FNAB seems highly representative of the tumor's genetic characteristics [2,17]. We considered that moving detection of monosomy 3 from the ex vivo to the in vivo arena may represent a relevant improvement in the clinical identification of this risk factor in patients affected by posterior uveal melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…FNAB has already been used to sample enucleated eyes to investigate cytogenetic abnormalities with promising results [2,17]. Therefore, the application of FISH to FNAB is considered a reliable method for detecting genetic prognostic parameters, and cytologic material obtained using FNAB seems highly representative of the tumor's genetic characteristics [2,17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting a little over a decade ago, investigators around the world began to report that chromosomal and transcriptional features of primary uveal melanoma cells were strongly associated with the pa tient's likelihood of developing subsequent extraophthalmic metastasis and metastatic death (25,(29)(30)(31)(32)(33)(34)(35) Several authors have shown that these chromosomal and transcriptional features can be determined on tumor specimens obtained by FNAB changing the indication for FNAB from purely diagnostic to investigational-prognostic (24,25,(36)(37)(38) . During the past few years, investigators from several of these centers have reported their experience with cytogenetic testing of the obtained FNAB aspirates (25,27,35,37,(39)(40)(41) .…”
Section: Prognostic Implications Of Cytopathologic Classification Of mentioning
confidence: 99%